Regularities and Factor of Expanding the Capacity of The Digital Educational Environment in Russia - Valentina P. SMORCHKOVA; Marina N. IGNATOVA; Liudmila V. MOSIENKO; Vasily A. DADALKO; Michael V. SHATOKHIN (Communications of International Proceedings, 2021)
The paper reveals the theoretical aspects and practical components of expanding the potential of the digital educational environment in Russia. The author substantiates the relevance and necessity of expanding the potential of the digital educational environment in the country, examines the features of the development of the infrastructure of the national digital educational environment, gives a comprehensive assessment of the state and level of digital literacy of the country's population, examines trends in the digitalization of the accounting and methodological base, materials, tools and services for the functioning of the domestic educational system. ... The results of the conclusions formed in the framework of the study and the identified patterns can be used to develop management initiatives at the state level aimed at expanding the potential of the national digital educational environment. Based on the results of the work, it is concluded that it is necessary to expand the potential of the digital educational environment, which in turn is the most important factor in the progressive socio-economic development of the state.
Keywords: Education; Digitalization; Digital Educational Environment; Distance Learning; Digital Literacy; Infrastructure of The Digital Educational Environment.